Processing method of suede product

By controlling the particle size and temperature of the foaming agent during the dip-coating process, a velvety surface is formed, solving the problems of poor hand feel and complex flocking process in dip-coated hangers, and achieving a velvety effect with good flexibility and strong resilience.

CN120838671APending Publication Date: 2025-10-28TAIZHOU SHUNYI NECESSITIES FACTORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511018790.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-23
Publication Date
2025-10-28

Smart Images

  • Figure CN120838671A_ABST
    Figure CN120838671A_ABST
Patent Text Reader

Abstract

The invention relates to a processing method of a suede product, and belongs to the technical field of plastic dipping processing. In order to solve the problem that existing flocking is prone to falling off, the processing method of the suede product is provided and comprises the steps that a pasty composite material is fed, and a metal framework heated to 200-220 DEG C is immersed into the composite material to be subjected to plastic dipping, so that the surface of a base body of the metal framework is coated with the composite material; after plastic dipping is completed, the metal framework is taken out upwards, then the metal framework subjected to plastic dipping is subjected to baking treatment under the condition that the temperature ranges from 180 DEG C to 186 DEG C, so that the surface of the coated composite material is foamed and broken to form a fluffy surface, and a corresponding fluffy product is obtained. According to the invention, the surface of the coated composite material can be foamed and broken, and part of the foaming body forms upwards-raised concave-convex surface combination, so that a suede effect that the surface is suede-shaped is formed on the whole; the formed material is good in flexibility, good in rebound resilience and good in hand feeling comfort.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a processing method for velvet products, belonging to the field of dip coating technology. Background Technology

[0002] To improve the quality of metal products, a coating is often applied to their surface for a better user experience. Some fitness equipment and everyday items benefit from this coating, offering advantages such as a comfortable feel and longer lifespan. For example, dumbbells are coated to improve the grip area, but this is often achieved by using anti-slip sleeves on the grip area, which can lead to slippage or loosening and falling off after prolonged use. Everyday items like clothes hangers, including wooden, plastic, and metal hangers, are commonly used. Metal hangers (usually made of wire) are particularly prevalent. To prevent oxidation and rust, plastic is typically coated onto the metal surface. This is usually done using a dip-coating process, where a heated metal wire hanger substrate is immersed in a plastic coating solution, allowing the plastic material to adhere to the surface. Heating then solidifies the coating. However, existing dip-coated hangers typically use PVC dip-coating liquid, resulting in a smooth or matte surface that is not pleasant to the touch, has poor skin-friendliness, and is prone to stickiness. Matte hangers, on the other hand, are difficult to produce and inefficient. To improve hanger quality, existing technologies involve flocking the surface. This involves electrostatically spraying adhesive onto the desired flocked areas of the wire hanger, masking the unflocked areas, and then applying the flock using electrostatic flocking. This method requires adhesive adhesion, and the electrostatic flocking process is complex, involves many steps, and is costly, making it unsuitable for industrial production. Furthermore, flocked products are prone to delamination or peeling during outdoor use and exposure to sunlight. Summary of the Invention

[0003] To address the shortcomings of the existing technology, this invention provides a method for processing suede products, solving the problem of how to achieve a suede-like surface that is not sticky to the touch.

[0004] The objective of this invention is achieved through the following technical solution: a method for processing suede products, characterized in that the method includes the following steps:

[0005] A. The slurry-like composite material is fed into the feedstock, wherein the composite material comprises the following components in parts by weight:

[0006] PVC paste resin: 20-45; plasticizer: 30-45; high-temperature resistant AC foaming agent: 10-15; stabilizer: 5-10; matte powder: 5-15; pigment: 10-15 parts; organic bentonite: 3-5; the high-temperature resistant AC foaming agent is a mixture of particles with a particle size of 40-45 mesh and particles with a particle size of 80-85 mesh, and the weight ratio of particles with a particle size of 40-45 mesh to particles with a particle size of 80-85 mesh is 3-4:1;

[0007] B. Immerse the metal skeleton heated to 200℃~220℃ into the composite material to perform dip coating, so that the composite material covers the surface of the metal skeleton matrix.

[0008] C. After the dip coating is complete, the metal skeleton is lifted upwards, and then the dip-coated metal skeleton is baked at a temperature of 180℃~186℃ to cause the surface of the coated composite material to foam and crack, forming a velvety surface to obtain the corresponding velvety product.

[0009] By synergistically improving the slurry-like composite material (or dip coating solution) and controlling the processing conditions, the composite material covering the metal skeleton surface is effectively foamed. This foaming and rupture on the surface creates a velvety surface characteristic. Some of the foamed material bulges upwards from the material surface and forms an uneven texture after cooling. The overall velvety surface is achieved through foaming and rupture, as well as the resulting uneven surface features. This is equivalent to the foaming and rupture on the surface of the composite material covering the metal skeleton during baking at 180℃~186℃, combined with the uneven texture formed by the upward bulge of some foamed material, resulting in a velvety surface effect. The resulting surface has good flexibility and resilience during use, providing a comfortable feel. It eliminates the need for additional flocking or other methods, as the velvety surface characteristic formed directly by material foaming effectively avoids the delamination and peeling issues associated with flocking. Compared to ordinary dip-coated products, which form a relatively smooth surface coating layer after dip coating and baking (without causing foaming, cracking, or uneven surface conditions), this invention utilizes surface foaming of the coating material to create a velvety surface.More specifically, this invention employs a high-temperature resistant AC foaming agent and a combination system of different particle sizes. Specifically, the high-temperature resistant AC foaming agent is a mixture of 40-45 mesh and 80-85 mesh particles, with a weight ratio of 3-4:1. This particle size distribution, combined with the addition of organic bentonite, allows for better suspension and uniform distribution of the foaming agent. Furthermore, utilizing this ratio of different particle sizes facilitates the formation of alternating particle sizes. The distributed system allows the gas within the foam formed on the surface of the foaming agent to expand during the foaming process, resulting in better foaming and rupture characteristics on the surface of the coated composite material. The smaller particle size of the foaming agent creates finer edges after rupture, better filling the gaps between the edges formed by the rupture of larger particle size foaming agents. The resulting small ruptured bubbles fill the gaps between the larger ruptured bubbles, thus achieving a more uniform foam edge and creating a uniformly distributed, velvety surface characteristic. The surface formed by the combined rupture and stacking of materials with varying particle sizes... It exhibits better elasticity, and by employing a higher proportion of small-particle-size foaming agents and a smaller proportion of large-particle-size foaming agents, it effectively ensures the material's toughness without affecting its overall toughness. If all foaming agents were used, the material's toughness would be poor. Furthermore, by selecting the appropriate foaming agent system materials and ensuring the baking temperature is maintained between 180℃ and 186℃ during processing, rapid foaming occurs on the material surface, leading to surface foam rupture and a velvety surface with good uniformity. This results in a seamless, velvety surface that requires no adhesive bonding. Suede products are characterized by their soft feel and good resilience. Furthermore, the addition of matte powder effectively absorbs the oils from plasticizers, preventing them from leaching out. This results in a non-sticky surface after foaming and suede application, providing a comfortable feel. Combined with a base material of PVC paste resin and plasticizers, the material itself is a paste-like liquid, suitable for use as a dip-coating solution. It also possesses good adhesion, allowing for excellent coating of the metal hanger surface and good flexibility. Pigments can be added according to specific color requirements, enabling the processing of products with various color specifications. The metal frame can be selected based on the product's needs. For example, when manufacturing fitness equipment, it can be the metal frame for dumbbells or the frame corresponding to the grip area of ​​other fitness equipment, which is then dip-coated to form the grip area. These metal products can also be everyday items, such as metal hangers and hooks, typically made of metal wire.

[0010] In the above-mentioned processing method for suede products, preferably, the metal frame in step B is a metal hanger. When the metal hanger is immersed, the time from the initial contact of the metal hanger with the slurry-like composite material surface to the completion of immersion is controlled within 30s to 40s. By controlling the time, the slurry-like composite material can be more evenly coated on the surface, and it can avoid the formation of excessively large air bubbles (non-foaming bubbles) due to rapid immersion, which would affect the subsequent foaming quality and cause excessively large depressions in the air-encapsulated areas, thus affecting surface properties.

[0011] In the above-mentioned processing method for suede products, preferably, after the dip coating is complete, the metal hanger is held for 3 to 5 seconds before being lifted upwards. Because a certain tension exists between the composite material and the hanger during the immersion of the metal hanger into the composite material, a concave liquid surface forms around the upper part of the metal hanger in contact with the composite material after complete dip coating. If the hanger is lifted upwards directly after complete dip coating, air will be trapped within the composite material on the metal hanger at this location, leading to defects such as bulging during baking. Therefore, by holding the hanger for 3 to 5 seconds after complete dip coating before lifting it upwards, the slurry-like composite material from other areas can flow back to fill the area with the concave liquid surface, allowing the liquid surface to return to its normal planar level. Lifting upwards then effectively avoids air trapping, ensuring the quality of subsequent foaming and resulting in a more uniform suede surface, preventing uneven suede distribution due to air presence. "After complete dip coating" refers to the state where the area of ​​the metal hanger requiring dip coating is fully immersed.

[0012] In the above-mentioned processing method for suede products, preferably, the baking time in step C is 5 to 7 minutes. Controlling the baking time is equivalent to adjusting the foaming time, which allows for more thorough and uniform surface foaming, and more uniform foam rupture, resulting in a better suede surface effect. As a further preferred option, the baking temperature in step C is 183°C to 185°C.

[0013] In the above-mentioned processing method for suede products, preferably, the high-temperature resistant AC foaming agent is selected from AC-2002 foaming agent and / or AC-2000 foaming agent. This enables the material to have good high-temperature resistance, and the decomposition temperature is higher than the baking temperature, thus better ensuring the foaming effect of the foaming agent.

[0014] In the above-mentioned processing method for suede products, preferably, the particle size of the matte powder in step A is 100-110 mesh. By controlling the particle size of the matte powder, it has a better oil absorption rate, further reduces the stickiness of the surface after foaming and suede formation, and gives the formed suede surface a non-sticky property and a comfortable surface feel.

[0015] In the above-mentioned processing method for suede products, preferably, the stabilizer in step A is a mixture of calcium-zinc stabilizer and organotin, wherein the weight ratio of calcium-zinc stabilizer to organotin is 1:0.1-0.3. This is beneficial for improving the stability of PVC materials at high temperatures and can also better coordinate the degree of foaming, achieving a more uniform foaming effect.

[0016] In the above-mentioned processing method for velvet products, preferably, the metal hanger in step B is a wire hanger made of iron wire, and the diameter of the iron wire in the wire hanger is 2.2 to 2.3 mm.

[0017] In the above-mentioned processing method for suede products, preferably, the plasticizer mentioned in step A is selected from one or more of diisooctyl terephthalate, diisononyl terephthalate, and di-n-octyl phthalate.

[0018] In summary, compared with the prior art, the present invention has the following advantages:

[0019] 1. By improving the slurry-like composite material (or dip coating liquid) and controlling the processing conditions, a synergistic effect can be achieved, which enables the surface of the coated composite material to foam and crack, and some foams to form an upwardly convex and uneven surface bond, resulting in a velvety surface effect. The resulting material has good flexibility, good resilience, and a comfortable feel, and does not require additional flocking or other methods, effectively preventing the phenomenon of falling off.

[0020] 2. By distributing the high-temperature resistant AC foaming agent in a system with different particle sizes and adding organic swelling agents, the foaming agent can be more evenly distributed on the surface. Using this ratio of particles of different sizes is beneficial to forming a system with alternating sizes, so that when the foaming agent foams, it can break up on the surface of the coating layer and partially form an upwardly convex and uneven surface bond. It can form a uniformly distributed, velvety surface characteristic. The edges formed after the foaming and breaking of the small-diameter foaming agent are more delicate, which can better fill the gaps between the edges formed by the foaming and breaking of the large-diameter foaming agent. The formed broken small bubbles can fill the gap area between the broken large bubbles, thereby making the foam edges on the surface more uniform.

[0021] 3. By using a larger proportion of small-particle-size foaming agents and a smaller proportion of large-particle-size foaming agents, the toughness of the material can be effectively guaranteed, so as not to affect the overall toughness of the material.

[0022] 4. This invention, by pausing for 3 to 5 seconds after complete dip coating and then lifting the metal hanger upwards, allows the slurry-like composite material from other locations to flow back into the area forming the concave liquid surface, restoring the liquid surface to its normal planar level. Lifting upwards then effectively avoids air encapsulation, ensuring the quality of subsequent foaming and resulting in a more uniform foamed surface, preventing uneven distribution of the nap due to air. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the surface and foam distribution of existing common foam materials after foaming.

[0024] Figure 2 This is an analytical diagram of the surface texture distribution of the foamed slurry composite material of the present invention observed under a microscope.

[0025] Figure 3 This is an analytical diagram of the cross-section of the foamed slurry composite material of the present invention observed under a microscope.

[0026] Figure 4 This is a structural schematic diagram of the velvet product of the present invention when it is a velvet hanger. Detailed Implementation

[0027] The technical solution of the present invention will be further described in detail below through specific embodiments, but the present invention is not limited to these embodiments.

[0028] Example 1

[0029] The processing method for this velvet product includes the following steps:

[0030] A slurry-like composite material (dipping liquid) is added to the storage tank of the dip coating equipment. This slurry-like composite material is a viscous slurry. The slurry-like composite material is fed into the storage tank at room temperature. The slurry-like composite material comprises the following components in parts by weight:

[0031] PVC paste resin: 20-45; plasticizer: 30-45; high-temperature resistant AC foaming agent: 10-15; stabilizer: 5-10; matte powder: 5-15; pigment: 10-15 parts; organic bentonite: 3-5; the high-temperature resistant AC foaming agent is a mixture of 40-45 mesh particles and 80-85 mesh particles, with a weight ratio of 3-4:1; the above-mentioned high-temperature resistant AC foaming agent can be an AC foaming agent with a decomposition temperature greater than 190℃ but less than 190℃, and further, AC-2000 foaming agent and / or AC-2002 foaming agent, etc., can be used.

[0032] For the PVC paste resin mentioned above, PVC-M31 paste resin is preferred. For the plasticizer, one or more of diisooctyl terephthalate (DOTP), diisononyl terephthalate, and di-n-octyl terephthalate can be used to improve the material's toughness. The following examples use diisooctyl terephthalate (DOTP) as an example for verification. The stabilizer is preferably a mixture of calcium-zinc stabilizer and organotin, with calcium-zinc stabilizer as the main component and organotin as the auxiliary component. This system is more conducive to uniform foam distribution, better control of the foaming degree, ensuring the overall foaming rate, and allowing for sufficient foaming. For the pigments mentioned above, different colors can be selected according to actual processing needs; there are no special limitations.

[0033] The cleaned metal frame is placed in a heating device and heated to 200℃~220℃. The portion of the metal frame to be dip-molded, preheated to 200℃~220℃, is then immersed in the aforementioned slurry-like composite material (dipping liquid) for dipping, ensuring the composite material fully coats the surface of the metal frame substrate. This is equivalent to coating the surface of the metal frame to be dip-molded with the aforementioned composite material, forming a coating layer. After complete dipping, the metal frame is slowly lifted from the surface of the dipping liquid, and then baked at 180℃~186℃. This causes the surface of the coated composite material to foam and rupture, forming a velvety surface, resulting in a velvety product. The velvety product surface also has some foamed material protruding upwards, forming an uneven velvety surface. Ideally, the baking time should be controlled to 5min~7min. This temperature control effectively ensures that the foam ruptures on the surface of the coating layer, achieving the velvety surface characteristic. The aforementioned velvety product can be fitness equipment or everyday items. For example, dumbbells used in fitness can have their entire outer surface coated with a plastic coating, and the grip parts of fitness equipment can also be coated with a velvet-like surface. Everyday items such as metal hangers and metal rods can also have their surfaces coated with a velvet-like surface. The metal frame mentioned above can be processed by stamping or metal wire processing, etc., and the processing method of the metal frame is not limited here.

[0034] The above-mentioned velvet product of the present invention can be effectively observed with the naked eye to form a velvety surface, and the overall distribution is dense and uniform; it has a comfortable feel when touched and is not sticky.

[0035] In a further embodiment, the composite material covering the metal skeleton surface is foamed during baking. Ideally, the average diameter of the foam cells distributed on the surface area is between 100 μm and 500 μm. This better ensures a velvety surface texture when the surface foam ruptures, and the unfoamed cells bulge upwards, creating an uneven surface characteristic after cooling and molding. The final velvety surface formed by foam rupture, combined with the uneven structural surface, results in a more compact and uniformly distributed overall surface, offering better comfort and superior resilience. Figure 1 and Figure 2 and Figure 3 As shown, Figure 1 This is a schematic diagram of the surface structure formed after foaming a common foam material. In common foaming, the foam cells are distributed internally and do not rupture on the surface, nor do they create upward bulges or uneven surface features. The surface of a typical foamed product is a generally continuous and relatively smooth surface; the foam cells do not rupture on the surface and do not bulge upwards to form uneven surfaces. (Combined with...) Figure 2 and Figure 3 As shown, the surface characteristics of the material (coating layer) of the suede product obtained by this invention require that the surface form foam ruptures and that some areas of the foam can bulge upwards from the surface, forming an uneven surface structure after cooling. This is equivalent to the foam forming on the surface during the foaming process expanding and rupturing outwards, thus causing the surface to crack, achieving a non-closed surface or an uneven surface structure, such as... Figure 2 and Figure 3 The image shows the surface characteristics observed under magnification using a microscope. Figure 2 This is a surface distribution analysis diagram magnified 50 times under a microscope. Figure 3 This is an analytical image magnified 100 times under a microscope. It shows the angle of the cross-section and the velvety surface characteristics observed under a microscope. It is not a flat, smooth surface. The velvety surface is formed by the rupture and bonding of foam cells, creating an uneven surface structure. Because the average diameter of the formed bubbles is relatively small before rupture, it can more effectively ensure that a dense, velvety surface feature is formed after the foam ruptures. Figure 3 The internal bubble structure at the cross-section can also be observed. After coating the surface of the wire hanger with the slurry-like composite material of the present invention, the desired velvet product is effectively formed by combining a dip-coating process and temperature control. The above... Figure 1 The surface structure shown is for illustrative purposes only, mainly to illustrate the state of the surface of ordinary foamed materials. Figure 2 and Figure 3 The analysis and comparison of different foaming and fluffing states of the coating layer surface after foaming of the slurry composite material of the present invention are presented; for Figure 1The foam formed during internal foaming is for illustrative purposes only and does not indicate a specific quantity distribution. When the slurry-like composite material of this application is combined with this process to coat the surface of the metal skeleton, a velvety product is finally formed, which is equivalent to the surface of the foamed composite material coating layer having a uniformly distributed velvety texture.

[0036] The shape of the metal frame can be customized according to actual needs. For example, if the aforementioned velvet product is a velvet coat hanger, it can be manufactured using... Figure 4 The shape of the hanger shown is processed, but there are no inherent limitations on the shape of the wire hanger.

[0037] Example 2

[0038] This velvet coat hanger comprises a wire hanger made of iron wire with a diameter of 2.2mm to 2.3mm, with a velvety, dip-coated material formed on the surface of the wire hanger. The specific manufacturing method can be as follows:

[0039] A slurry-like composite material (dipping liquid) is added to the storage tank of the dip coating equipment; this slurry-like composite material is a viscous slurry, prepared by the following materials. The aforementioned slurry-like composite material comprises the following components in parts by weight:

[0040] PVC paste resin: 45, here the PVC paste resin is PVC-M31; plasticizer: 45, the plasticizer is DOTP; high temperature resistant AC foaming agent: 15; stabilizer: 10; matte powder: 10; pigment: 10; organobentonite: 3-5; the above high temperature resistant AC foaming agent is AC-2000 foaming agent, and it is a mixture of 40 mesh particles and 80 mesh particles, and the weight ratio of 40 mesh particles to 80 mesh particles is 4:1; the above stabilizer is a mixture of calcium zinc stabilizer and organotin, and the weight ratio of calcium zinc stabilizer to organotin is 1:0.1; the matte powder is Korean LGLB-100M; the particle size of the matte powder is 100 mesh.

[0041] The wire hanger is placed in a heating device and heated to 200℃~220℃. After heating, the wire hanger is slowly immersed in the above-mentioned slurry-like composite material for dip coating, so that the composite material covers the surface of the wire hanger substrate. During the dip coating process, the time from the moment the wire hanger first contacts the surface of the slurry-like composite material (i.e., just after immersion) to the completion of immersion is controlled within 30s~40s, so that the area of ​​the wire hanger to be dipped is completely coated. After complete coating, it is held still for 5s, and then the wire hanger is slowly lifted upwards from the surface of the coating liquid. After dripping (even if the coating material stops dripping after surface coating), the composite material forms a coating on the area of ​​the wire hanger to be dipped. It is then transferred to the baking system, where the dipped wire hanger is baked at a temperature of 180℃~182℃ for 7 minutes to allow foaming and curing, and to cause the foamed surface of the coated composite material to rupture and form a velvety surface. After baking, it is transported out of the baking system for natural cooling, and the corresponding velvety hanger is produced.

[0042] By observing with the naked eye and feeling with the hand, it can be determined that the surface of the velvet hanger has a velvety surface characteristic, and has good overall flexibility, a comfortable feel, and is not sticky to the hand.

[0043] The prepared velvet hanger was placed on a flat work surface, and a 10kg weight was applied to the entire velvet surface of the hanger for 48 hours. The results showed that after 48 hours of pressure, the velvet surface of the hanger could rebound without being flattened or broken. This indicates that the velvet surface of the hanger obtained by this method has the advantages of good flexibility, excellent rebound performance, good overall toughness of the material, and is not easy to break.

[0044] Example 3

[0045] This velvet coat hanger comprises a wire hanger made of iron wire with a diameter of 2.2mm to 2.3mm, with a velvety, dip-coated material formed on the surface of the wire hanger. The specific manufacturing method can be as follows:

[0046] A slurry-like composite material (dipping liquid) is added to the storage tank of the dip coating equipment; this slurry-like composite material is a slurry with a certain viscosity, which can be prepared by the following materials. The aforementioned slurry-like composite material includes the following components in parts by weight:

[0047] PVC paste resin: 30, here the PVC paste resin is PVC-M31; plasticizer: 40, the plasticizer is DOTP; high temperature resistant AC foaming agent: 12; stabilizer: 8; matte powder: 15; pigment: 10; organobentonite: 3; the above high temperature resistant AC foaming agent is AC-2000 foaming agent, and it is a mixture of 40 mesh particles and 80 mesh particles, and the weight ratio of 40 mesh particles to 80 mesh particles is 3:1; the above stabilizer is a mixture of calcium zinc stabilizer and organotin, and the weight ratio of calcium zinc stabilizer to organotin is 1:0.3; the matte powder is Korean LGLB-100M, and the particle size of the matte powder is 110 mesh.

[0048] The wire hanger is placed in a heating device and heated to 200℃~220℃. After heating, the wire hanger is slowly immersed in the above-mentioned slurry-like composite material for dip coating, so that the composite material covers the surface of the wire hanger substrate. During the dip coating process, the time from the moment the wire hanger first contacts the surface of the slurry-like composite material (i.e., just after immersion) to the completion of immersion is controlled within 35s~40s, so that the area of ​​the wire hanger to be dipped is completely coated. After complete coating, it is held still for 3s, and then the wire hanger is slowly lifted upwards from the surface of the coating liquid. After dripping (even if the coating material stops dripping after surface coating), the composite material forms a coating on the area of ​​the wire hanger to be dipped. It is then transferred to the baking system, where the dipped wire hanger is baked at a temperature of 183℃~186℃ for 6 minutes to allow foaming and curing, and to cause the foamed surface of the coated composite material to rupture and form a velvety surface. After baking, it is transported out of the baking system for natural cooling, and the corresponding velvety hanger is produced.

[0049] By observing with the naked eye and feeling with the hand, it can be determined that the surface of the velvet hanger has a velvety surface characteristic, and has good overall flexibility, a comfortable feel, and is not sticky to the hand.

[0050] The prepared velvet hanger was placed on a flat work surface, and a 10kg weight was applied to the entire velvet surface of the hanger for 48 hours. The results showed that after 48 hours of pressure, the velvet surface of the hanger could rebound without being flattened or broken. This indicates that the velvet surface of the hanger obtained by this method has the advantages of good flexibility, excellent rebound performance, good overall toughness of the material, and is not easy to break.

[0051] Example 4

[0052] This velvet coat hanger consists of a wire hanger made of iron wire with a diameter of 2.2mm, with a velvety, dip-coated material formed on the surface of the wire hanger. The specific manufacturing method can be as follows:

[0053] A slurry-like composite material (dipping liquid) is added to the storage tank of the dip coating equipment; this slurry-like composite material is a slurry with a certain viscosity, which can be prepared by the following materials. The aforementioned slurry-like composite material includes the following components in parts by weight:

[0054] PVC paste resin: 20, here the PVC paste resin is PVC-M31; plasticizer: 30, the plasticizer is DOTP; high temperature resistant AC foaming agent: 10; stabilizer: 5; matte powder: 5; pigment: 12; organobentonite: 4; the above high temperature resistant AC foaming agent is AC-2002 foaming agent, and it is a mixture of 45 mesh particles and 85 mesh particles, and the weight ratio of 45 mesh particles to 85 mesh particles is 4:1; the above stabilizer is a mixture of calcium zinc stabilizer and organotin, and the weight ratio of calcium zinc stabilizer to organotin is 1:0.2; the matte powder is Korean LGLB-100M, and the particle size of the matte powder is 100 mesh.

[0055] The wire hanger is placed in a heating device and heated to 200℃~220℃. After heating, the wire hanger is slowly immersed in the above-mentioned slurry-like composite material for dip coating, so that the composite material covers the surface of the wire hanger substrate. During the dip coating process, the time from the moment the wire hanger first contacts the surface of the slurry-like composite material (i.e., just after immersion) to the completion of immersion is controlled within 35 seconds, so that the area of ​​the wire hanger to be dipped is completely coated. After complete coating, it is held still for 5 seconds, and then the wire hanger is slowly lifted upwards from the surface of the coating liquid. After dripping (even if the coating material stops dripping after surface coating), the composite material forms a coating on the area of ​​the wire hanger to be dipped. It is then transferred to the baking system, and the coated wire hanger is baked at a temperature of 182℃ for 6 minutes to cure and cause the surface of the coated composite material to foam and crack to form a velvety surface. After baking, it is transported out of the baking system for natural cooling to produce the corresponding velvety hanger.

[0056] By observing with the naked eye and feeling with the hand, it can be determined that the surface of the velvet hanger has a velvety surface characteristic, and has good overall flexibility, a comfortable feel, and is not sticky to the hand.

[0057] The prepared velvet hanger was placed on a flat work surface, and a 10kg weight was applied to the entire velvet surface of the hanger for 48 hours. The results showed that after 48 hours of pressure, the velvet surface of the hanger could rebound without being flattened or broken. This indicates that the velvet surface of the hanger obtained by this method has the advantages of good flexibility, excellent rebound performance, good overall toughness of the material, and is not easy to break.

[0058] The specific embodiments described in this invention are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.

[0059] Although the present invention has been described in detail and specific embodiments have been cited, it will be apparent to those skilled in the art that various changes or modifications can be made without departing from the spirit and scope of the invention.

Claims

1. A method for processing suede products, characterized in that, The method includes the following steps: A. The slurry-like composite material is fed into the feedstock, wherein the composite material comprises the following components in parts by weight: PVC paste resin: 20-45; plasticizer: 30-45; high-temperature resistant AC foaming agent: 10-15; stabilizer: 5-10; matte powder: 5-15; pigment: 10-15; organic bentonite: 3-5; the high-temperature resistant AC foaming agent is a mixture of particles with a particle size of 40-45 mesh and particles with a particle size of 80-85 mesh, and the weight ratio of particles with a particle size of 40-45 mesh to particles with a particle size of 80-85 mesh is 3-4:1; B. Immerse the metal skeleton heated to 200℃~220℃ into the composite material to perform dip coating, so that the composite material covers the surface of the metal skeleton matrix. C. After the dip coating is complete, the metal skeleton is lifted upwards, and then the dip-coated metal skeleton is baked at a temperature of 180℃~186℃ to cause the surface of the coated composite material to foam and crack, forming a velvety surface to obtain the corresponding velvety product.

2. The processing method for the suede product according to claim 1, characterized in that, The metal frame mentioned in step B is a metal hanger. When the metal hanger is immersed, the time from the initial contact of the metal hanger with the slurry-like surface of the composite material to the completion of immersion is controlled within 30s to 40s.

3. The processing method for the suede product according to claim 2, characterized in that, After the dip coating is complete, hold for 3 to 5 seconds, then lift the metal hanger upwards.

4. The processing method for the suede product according to claim 1, characterized in that, The baking time in step C is 5 to 7 minutes.

5. The processing method for the suede product according to claim 4, characterized in that, The baking temperature in step C is 183℃~185℃.

6. A method for processing suede products according to any one of claims 1-5, characterized in that, The high-temperature resistant AC foaming agent is selected from AC-2002 foaming agent and / or AC-2000 foaming agent.

7. The processing method of the suede product according to any one of claims 1-5, characterized in that, The particle size of the matte powder mentioned in step A is 100 mesh to 110 mesh.

8. The processing method for the suede product according to claim 7, characterized in that, The stabilizer mentioned in step A is a mixture of calcium-zinc stabilizer and organotin, wherein the weight ratio of calcium-zinc stabilizer to organotin is 1:0.1 to 0.

3.

9. The processing method for the suede product according to claim 2, characterized in that, The metal hanger mentioned in step B is a wire hanger.

10. The processing method of the suede product according to claim 1, characterized in that, The metal frame is a fitness device, the fitness device is a dumbbell, and the dumbbell is made of metal.